Implementing Ultra–Fast-Track Cardiac Anesthesia in Minimally Invasive Cardiac Surgery - Jiang, Tian; Xu, Linting; Zheng, Qinghui; Zhang, Yihui; Wang, Shuaibing; Wang, Yu; Lou, Xiaokan; Yan, Meijuan; Wei, Hanwei (Journal of cardiothoracic and vascular anesthesia, 2025)
To analyze factors influencing the implementation of ultra–fast-track cardiac anesthesia (UFTCA) from the perspectives of preoperative and intraoperative conditions and to compare its postoperative recovery with that of conventional cardiac anesthesia (CGA). An observational retrospective study Electronic medical records data for patients from January 2021 through July 2023 967 patients with a documented history of minimally invasive cardiac surgery (MICS) Review of electronic medical records Data for 947 patients, including 439 who received UFTCA and 508 who received CGA, were analyzed retrospectively. Multivariate logistic regression identified independent factors associated with UFTCA implementation. Risk factor analysis showed that age >50 years (odds ratio [OR], 1.924; p = 0.040), history of stroke (OR, 2.290; p = 0.009), and duration of cardiopulmonary bypass (CPB) (OR, 1.013; p < 0.001), intraoperative sufentanil dosage (OR, 1.035; p < .001), and surgeries ending after 8 pm (OR, 2.184; p < 0.001) were negatively correlated with UFTCA implementation. Pectoral muscle fascial plane block (OR, 0.120; p < .001) and dexamethasone (OR, 0.438; p < .001) were positive factors in UFTCA implementation. Compared to the CGA group, the UFTCA group had fewer cases of intensive care unit (ICU) rescue analgesia (77 [17.5%] vs 178 [35%]; p < 0.001), shorter ICU stay (mean, 22.83 ± 20 hours vs 44 ± 43 hours; p < 0.001) and postoperative hospital stay (mean, 8 ± 3 days vs 10 ± 5 d; p < .001), and lower incidence of postoperative delirium (6 [1.4%] vs 28 [5.5%]; p = 0.001) but a higher incidence of postoperative nausea and vomiting (86 [19.6%] vs 62 [12.2%]; p = 0.002). The oxygenation index (OI) was lower at 1 hour postsurgery but higher at 6 hours postsurgery in the UTCA group compared to the CGA group (p < 0.05). Seven independent factors were identified for UFTCA implementation in MICS, among which age >50 years, history of stroke, duration of CPB, intraoperative sufentanil dosage, and surgery ending after 8 pm were negative factors and pectoral muscle fascial plane block and dexamethasone use were positive factors. The use of UFTCA in MICS shortened ICU stay and hospital stay, decreased the incidence of delirium, and promoted postoperative pulmonary function.